2003
DOI: 10.1046/j.1467-7652.2003.00021.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Arabidopsis ADS1 gene in Brassica juncea results in a decreased level of total saturated fatty acids

Abstract: SummaryBrassica juncea plants transformed with the Arabidopsis ADS1 gene, which encodes a plant homologue of the mammalian and yeast acyl-CoA ∆9 desaturases and the cyanobateria acyl-lipid ∆9 desaturase, were found to have a statistically significant decrease in the level of saturated fatty acids in seeds. The decrease in the level of saturated fatty acids is largely attributable to decreases in palmitic acid (16:0) The present study provides preliminary experimental data suggesting that the Arabidopsis ADS1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…The physiological functions of ADS enzymes other than FAD5, including those of ADS1 and ADS2, remain to be determined. ADS1 and ADS2 have been demonstrated to be functional fatty acid desaturases (Yao et al, 2003;Heilmann et al, 2004) that lack transit peptides and likely reside in the endoplasmic reticulum. ADS1 and ADS2 gene expression levels are differentially regulated in response to changes in ambient temperature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The physiological functions of ADS enzymes other than FAD5, including those of ADS1 and ADS2, remain to be determined. ADS1 and ADS2 have been demonstrated to be functional fatty acid desaturases (Yao et al, 2003;Heilmann et al, 2004) that lack transit peptides and likely reside in the endoplasmic reticulum. ADS1 and ADS2 gene expression levels are differentially regulated in response to changes in ambient temperature.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of membrane lipid unsaturation influences the biophysical properties of membranes at high or low temperatures (Nishida and Murata, 1996), suggesting a role for ADS1 and ADS2 in temperature acclimation of Arabidopsis reproductive organs (Nishida and Murata, 1996). Although characterized as D9-desaturases in yeast and in seeds of Arabidopsis (Heilmann et al, 2004) and B. juncea (ADS1 only; Yao et al, 2003), the data presented here show that, when retargeted to the plastid, ADS1 and ADS2 can act as palmitoyl-MGDG D7-desaturases and functionally complement the fad5 mutation. The molecular mechanism underlying this apparent switch in regiospecificity has recently been shown to involve interactions between desaturases and different head groups of the lipid substrates found in different subcellular compartments (Heilmann et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seeds from transformed plants contained decreased levels of saturated fatty acids and a slight increase in oleic acid content (Yao et al, 2003). Although the evidence was indirect, the results suggested that AtADS1 may encode a D9 desaturase.…”
mentioning
confidence: 94%
“…-desaturated fatty acids when expressed in yeast, Arabidopsis, or Brassica juncea (Yao et al, 2003;Heilmann et al, 2004b). ADS3, another member of the Arabidopsis ADS-like gene family, was identified as encoding the FAD5 palmitoylmonogalactosyldiacylglycerol D…”
mentioning
confidence: 99%